Implementasi ERP Pada Pengelolaan Transaksi Dan Inventaris Di Fourteen Adventure Menggunakan Metode RAD - Resta Klendifa Jatiasih; Sisilia Thya Safitri (Telkom University, 2026)
This study addresses transaction and inventory management problems at Fourteen Adventure, a rental service UMKM, where manual recording using written notes and spreadsheets caused data inaccuracies and delays. Data were collected through interviews with the head of the store, direct observation of business processes, and system evaluation using User Acceptance Testing (UAT). The proposed solution is the implementation of an ERP system based on Odoo using the Rapid Application Development (RAD) method, which consists of requirement planning, RAD design workshop, and implementation stages. System functionality was evaluated using Black Box Testing, while user satisfaction was measured through UAT involving key internal users. The results show that the system achieved 100% functional validity and demonstrated high usability, improving the accuracy of transaction and inventory recording, reducing manual errors, and enabling real-time stock monitoring. UAT results indicate that the system was perceived as very good by the head of the store (84.8%) and good by sales staff (73.4%), indicating successful adoption and positive operational impact